Winding orientation method to minimise the secondary leakage of a gapped transformer utilised in LLC resonant converter. Issue 3 (1st February 2018) - Noah, M.; Umetani, K.; Yamamoto, M.; Imaoka, J.
Abstract : It is a common practice in the LLC resonant converter to utilise the transformer leakage inductance as an inductive component in the resonant tank. Nonetheless, the leakage does not exist only on the primary side but also on the secondary side. This Letter proposes a winding orientation method to minimise the undesirable secondary leakage in the transformer. The basic theory of the proposed method relies on Dowell's model and Ampere's law to minimise the stored magnetic energy originated from the secondary windings. Along with the theoretical analysis, experimental tests have been conducted to evaluate the proposed method. The measurements of the leakage inductance are consistent with the expectations of the proposed winding orientation method.